2002
DOI: 10.1119/1.1435346
|View full text |Cite
|
Sign up to set email alerts
|

Teaching quantum mechanics on an introductory level

Abstract: We present a new research-based course on quantum mechanics in which the conceptual issues of quantum mechanics are taught at an introductory level. In the context of virtual laboratories, the students discover from the very beginning how quantum phenomena deviate from our classical everyday experience. The results of the evaluation of the course show that most of the students acquired appropriate quantum mechanical conceptions, and that many of the common misconceptions encountered in traditional instruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
171
4
36

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(216 citation statements)
references
References 9 publications
5
171
4
36
Order By: Relevance
“…The term orbital is coined for the locations that have a high possibility of finding electrons. In this study, the orbital model was adapted from the study of Müller and Wiesner (2002) and Harrison and Treagust (1996). Even though many models and ideas emerged during the process of historical development of the atom concept, the literature showed that the students were still not clear about it.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The term orbital is coined for the locations that have a high possibility of finding electrons. In this study, the orbital model was adapted from the study of Müller and Wiesner (2002) and Harrison and Treagust (1996). Even though many models and ideas emerged during the process of historical development of the atom concept, the literature showed that the students were still not clear about it.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Como já argumentado anteriormente (OSTERMANN et al, 2006;PEREIRA et al, 2009), o IVMZ pode ser uma poderosa ferramenta para a discussão de conceitos fundamentais da FQ, tanto que o interferômetro de MZ tem sido utilizado por muitos autores como ponto de partida para tal ADAMS, 1998;SCARANI, 1998;HOLBROW et al, 2002;MÜLLER;WIESNER, 2002;PESSOA JR., 2003;GALVEZ et al, 2005;PRADO, 2005;OSTERMANN et al, 2006;SCARANI, 2006;DIMITROVA;WEIS, 2008;PEREIRA et al, 2009;DIMITROVA;WEIS, 2010;FERRARI;BRAUNECKER, 2010;GALVEZ, 2010). Para que esse dispositivo óptico possa realizar um experimento que permita a discussão sobre fundamentos da FQ, é preciso considerar que a fonte de laser seja monofotônica, ou seja, emite a cada vez um pulso de onda que tem a potencialidade de gerar um único fóton em um detector de eficiência máxima.…”
Section: O Interferômetro De Mach-zehnderunclassified
“…Bancadas virtuais que exploram o IMZ em regimes clássico e quântico para o ensino da FQ introdutória são temas relativamente recentes na literatura voltada ao ensino de FQ, como por exemplo, o IMZ de Müller e Wiesner [6,7]. Desenvolvemos uma versão mais completa do IMZ em relaçãoà do software de Müller e Wiesner, com correções de alguns bugs de programação que havia no software citado e importantes generalizações do arranjo considerado, além de inúmeras possibilidades novas de uso de polaróides e de detectores, tanto em regime clássico quanto em regime quântico.…”
Section: Introductionunclassified
“…Ressaltamos que o IMZ em regime clássico pode servir como excelente ponto de partida para a discussão da dualidade onda-partícula na FQ, graças ao fato de que perguntas tais como por qual braço rumou o fóton? [3][4][5][6][7][8][9][10] são mais naturalmente provocadas por esse arranjo.…”
Section: Introductionunclassified